The Role of Baznas' Productive Zakat Assistance in The Development of MSMES in Gorontalo Province - Neva Lionitha Ibrahim; Vita Imam M. Solikhah; Heldy Vanni Alam (Global Scientific Publishing, 2023)
This research aims to review the role of the National Amil Zakat Agency (BAZNAS) of Gorontalo Province in developing the Micro, Small and Medium Enterprises (UMKM) through the Productive Zakat Program in Gorontalo Province. The research used Descriptive Qualitative research method. The focus (indicators) of the research are 1) The role of Productive Zakat Support in developing MSMEs in Gorontalo Province 2) The development of MSMEs in Gorontalo Province before and after receiving productive zakat assistance from BAZNAS Gorontalo Province, 3) The obstacles faced in developing MSMEs through the productive zakat program of BAZNAS Gorontalo Province. The results showed that the role of BAZNAS in developing MSMEs is by distributing zakat in the form of business capital assistance to mustahik in order to help and encourage the community (who deserve assistance) both from entrepreneurs and non-entrepreneurs who need capital so that it will indirectly improve the quality of MSMEs in Gorontalo Province. The impact of BAZNAS productive zakat directly for the development of MSMEs are: 1) Increase the number of business goods, 2) Increase customer purchasing interest in MSMEs that receive assistance, 3) Increase the amount of production, 4) Increase sales turnover (income ), 5) Increase business capital and 6) Increase the motivation of beneficiaries (UMKM owners) in developing businesses. The obstacles that occur during the distribution of zakat in the productive zakat program are miscommunication between BAZNAS and the beneficiaries and there is also a mismatch between the data of prospective beneficiaries and reality and the distribution process which tends to be complicated and takes a long time.
Keywords: Role; Productive Zakat; Gorontalo Province Amil Zakat Agency